Temporal location of high-intensity interval training in cycling does not impact the time spent near maximal oxygen consumption - Mckee, J. R.; Wall, B. A.; Peiffer, J. J. (International Journal of Sports Physiology and Performance, 2021)
Purpose: To examine the influence of temporal location of high-intensity interval training (HIIT) within a cycling session on the time spent =90% of maximal oxygen consumption and physiological and perceptual responses.